THE EFFECTS OF EXERCISE MODELS ON HEMATOLOGICAL PROFILE AND MEET PHYSICAL QUALITY IN GARUT SHEEP - Ronnie Permana; Mohamad Yamin; Rudy Priyanto; Asep Gunawan; Dewi Apri Astuti (Jurnal Kedokteran Hewan, 2020)
The objective of this study was to evaluate the effect of exercise levels on the hematological and metabolical status, and carcass quality of Garut sheep. In total 24 of Garut sheep used in this study. The levels of exercise contain three treatments namely non exercise, semi exercise  and exercise. Blood collection through the jugular vein of sheep samples was carried out at the end of the study, using a 5 mL EDTA tube to measure the haematological condition of the animal sample. Likewise, collecting muscle samples to determine the physical quality of meat.The data was analyzed by analysis of variance and continued by Duncan test for a post hoc test. The results showed that the models of exercise were not significantly (P0.05) affected to hematological level and also carccas quality including juiceness, tenderness, drip loss and water holding capacity. Organoleptic sensory  using semiexercise was more favourable meat  compare to exercise and non exercise. While for the colour of meat, non exercise treatment was significantly (P0.05) affected to the colour of meat compare to exercise and semi exercise. Furthermore the semi exercise  was the best treatment to produce fresh taste meat with good sensory characteristic.